A comparison of the wind spectrum according to different methods - an original project of a building on a cliff in Gdynia - Zielińska, Monika; Zarychta, Karolina (Zielona Góra: Uniwersytet Zielonogórski)
The article presents numerical simulations of the dynamic wind loads on the structure of a building designed on a cliff in Gdynia. The results obtained from the two methods: Davenport`s and Karman`s are compared. The results allowed a comparison of the two methods, and they provided an answer to the question how a construction, designed in such an unusual condition of a cliff behaves under the influence of the gusting wind. The wind spectrum is presented and compared in both directions: of the X-axis and of the Y-axis. The dynamic calculations are carried out in the Abaqus software. The conducted numerical analyses compare the displacements in two points - at half height of the building and at the top - obtained by the two methods.
Keywords: wind spectrum; Davenport; Karman; cliff; dynamic analysis; modal analysis; FEM